The relationship between lung disease severity and the sputum proteome in cystic fibrosis. (November 2022) - Maher, Rosemary E.; Barrett, Emma; Beynon, Robert J.; Harman, Victoria M.; Jones, Andrew M.; McNamara, Paul S.; Smith, Jaclyn A.; Lord, Robert W.
Abstract: Background: Proteomics can reveal molecular pathways of disease and provide translational perspectives to inform clinical decision making. Although several studies have previously reported the cystic fibrosis airway proteome, the relationship with severity of lung disease has not been characterised. The objectives of this observational study were to investigate differences in the CF sputum proteome associated with disease severity and identify potential markers of disease with translational potential. Methods: Sputum samples from healthy volunteers and cystic fibrosis subjects (some prescribed modulator therapies) were analysed using liquid-chromatography tandem mass spectrometry. Severity of lung disease was based on baseline spirometry (percentage predicted forced expiratory volume in 1 s, FEV1%). Results: Multiple sputum proteins (108 increased; 202 decreased) were differentially expressed in CF (n = 38) and healthy volunteers (n = 32). Using principal component analysis and hierarchical clustering, differences in sputum proteome were observed associated with progressive lung function impairment. In CF subjects, baseline FEV1% correlated with 87 proteins (positive correlation n = 20, negative n = 67); most were either neutrophil derived, or opposed neutrophil-driven oxidant and protease activity. Conclusion: Predictable and quantifiable changes in the CF sputum proteome occurred associated with progressive lung function impairment, some of which might have value as markers of disease severity in CF sputum. Further work validating these markers in other patient cohorts and exploring their clinical utility is needed. Highlights: There are differences in sputum proteome between CF subjects and healthy volunteers. The proteome differences become more pronounced with worsening CF lung disease. Differences relate to increased neutrophil activity and counterregulatory responses. Some of these proteins might have value as markers of CF lung disease severity.